Seismicity Evaluation of Central and Southern Iraq - Abd Alridha, Nawal; Jasem, Noor (Iraqi Journal of Science, 2024)
This study covers the area bounded by latitudes 29° to 34° N and longitudes 39° to 48°E.The seismicity of area for the period 1980–2011 is evaluated. In this study the geological and topography were performed, regarding the historical seismicity. More than (145) events were re-analyzed in Iraqi Seismological Network (ISN) and the recorded data was subjected to statistical analysis. This study shows high activity in the east and very low activity in the west.